The emergence and influence of the customer experience in the context of sustainable consumption - Balo, Bidyut Kumer; Jaakkola, Elina; Aleem, Majid; Sandberg, Birgitta (Springer, 2026)
Despite their evident mutual relevance and interconnection, systematic examinations of the relationship between customer experience (CX) and sustainable consumption are rare. This systematic literature review explores the intersection of these concepts by analyzing the nature and influence of CX in sustainable consumption. First, the study synthesizes existing research knowledge on CX stimuli that are particularly highlighted in the context of sustainable consumption, such as product elements and sensory cues tied to sustainability, eco-conscious advertising and marketing messages, and bio-based packaging elements. Second, the review charts CX dimensions evoked by sustainability stimuli, including various sensory, affective, cognitive, and social experiences. Third, the study describes the role of CX in promoting or hindering both purchase behaviors, such as purchasing organic offerings, and non-purchase behaviors, such as recycling. The findings confirm the relevance of CX in facilitating transaction-focused outcomes (purchases or sales), but also show that CX can influence non-transactional outcomes, such as engagement and disengagement in sustainability practices. The study advances existing CX research by developing a conceptual framework that delineates CX in the sustainable consumption context and identifying special features and tensions related to it. Furthermore, the study adopts a dynamic and processual approach to understanding consumer behavior in the context of sustainable consumption, departing from traditional knowledge, awareness, and practice-based approaches. It highlights the interplay between CX stimuli and outcomes, not only in purchase decisions but also in non-purchase journeys, such as sharing. The findings highlight significant gaps in the current literature, including the need for more attention to the economic, social, and cultural dimensions of sustainable consumption, alongside the environmental dimensions that have been more commonly studied. Building on identified gaps in existing research and the developed propositions, our study sets the stage for future research on CX in the context of sustainable consumption.